Parental attitudes in child maltreatment - Camilo, C. (2020)
An information-processing approach to maladaptive parenting suggests that high-risk and maltreating parents are likely to hold inaccurate and biased preexisting cognitive schemata about child development and child rearing. Importantly, these schemas, which may include values, beliefs, expectations, and attitudes, are known to influence the way parents perceive and subsequently act toward their children. However, the few studies specifically addressing parental attitudes only considered global maltreatment, not distinguishing abuse from neglect. Moreover, few have considered dual-process models of cognition, relying mostly on the explicit level of parental attitudes that can be prone to various biases. Based on the Social Information Processing (SIP) model of child abuse and neglect, this study examines the association of parents preexisting cognitive schemata, namely explicit and implicit parental attitudes, and child abuse and neglect. A convenience sample of 201 mothers (half with at least one child referred to child protection services) completed a measure of explicit parental attitudes and a speed-accuracy task related to parenting. Abuse and neglect were measured with self-report and professionals-report instruments. Overall, the results support the hypothesis that maladaptive parenting is related with more biased preexisting cognitive schemas, namely attitudes related to parenting, but only for neglect and particularly when reported by professionals. Moreover, the results observed with both the explicit and implicit measures of attitudes were convergent, with mothers presenting more inadequate explicit attitudes also exhibiting an overall lower performance in the implicit attitudes task. This study is likely to contribute to the SIP framework of child abuse and neglect, particularly for the elucidation of the sociocognitive factors underlying maladaptive parenting, while also providing relevant cues for prevention and intervention programs.